Counterfeit and falsified medicines in the EU : a legal perspective - Kohli, Vishv Priya (Elgar studies in health and the law series, 2021)
"This timely book investigates the issue of counterfeit and falsified medicines (CFM) in the EU, identifying that this is a problem that lies at the intersection of three spheres of law - medicine, intellectual property (IP), and criminal law. The book highlights key issues such as infiltration of the legal supply chain and the involvement of organised crime, analysing relevant EU law and demonstrating the challenges of CFM. Using examples from several case studies, Vishv Priya Kohli reveals the gaps in the current legal framework, underlining the particular difficulties created by the interplay between different areas of law as well as the lack of criminal penalties. The author explores areas where improvements have already been made, in particular through the Falsified Medicines Directive, and articulates a number of recommendations to fill in the gaps, for example by harmonizing criminal law and building synergies within law enforcement. Counterfeit and Falsified Medicines in the EU will be of great interest to academics and students in IP, health and medical law, and criminal law in the EU. It will also prove valuable for practitioners and policymakers working in and with enforcement authorities in the EU, as well as those working in the medical field itself"--